Nickel-cobalt metal-based wear-resistant and corrosion-resistant coating and preparation method thereof

Through multi-layer gradient spraying and laser micro-texturing treatment, the nickel-cobalt alloy coating achieves a comprehensive improvement in high strength, toughness, corrosion resistance and hydrophobicity under extreme environments, solving the problem of easy corrosion of traditional coatings in extreme environments.

CN120758824AActive Publication Date: 2025-10-10YANTAI HUAHENG ENERGY SAVING TECH CO LTD

Patent Information

Application Number
CN202511287629.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-10
Publication Date
2025-10-10
Estimated Expiration
2045-09-10

AI Technical Summary

Technical Problem

Existing nickel-cobalt alloy coatings are prone to penetration of corrosive media due to high porosity and weak interlayer bonding in extreme environments. Traditional modification methods fail to give the coating hydrophobic properties, resulting in insufficient wear resistance and corrosion resistance.

Method used

Multi-layer gradient spraying combined with interlayer laser micro-texturing treatment is used to form a regular micro-pit array, enhance the interlayer bonding strength, and achieve hydrophobicity through a micro-nano composite structure, avoiding external hydrophobic additives.

Benefits of technology

Significantly improve the wear resistance, corrosion resistance and hydrophobicity of the coating, increase the interlayer bonding strength, extend the penetration path of the corrosive medium, and increase the hydrophobic mechanical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120758824A_ABST
    Figure CN120758824A_ABST
Patent Text Reader

Abstract

The invention discloses a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating and a preparation method thereof, and relates to the technical field of surface coatings, and the technical key points of the nickel-cobalt metal-based wear-resistant and corrosion-resistant coating comprise the following steps: S1, carrying out oil removal and sand blasting roughening treatment on the surface of a metal substrate, then cleaning with absolute ethyl alcohol, and drying; s2, nickel-cobalt metal-based alloy powder is prepared, wherein the nickel-cobalt metal-based alloy powder is prepared from, by weight, 55-65 parts of nickel, 20-30 parts of cobalt, 15-18 parts of chromium, 4-6 parts of molybdenum, 3-5 parts of tungsten, 1-3 parts of iron, 0.8-1.5 parts of silicon, 0.5-1.2 parts of carbon and 0.5-1.0 part of boron; the technical effect is that a regular non-smooth micro-pit array is manufactured on the surface of a sprayed layer through interlayer laser micro-texturing treatment. And the molten particles of the next layer of spraying material are embedded into the micro pits to form a strong mechanical interlocking effect, so that the interlayer bonding strength and the anti-shearing capability are greatly improved, and interlayer dislocation and stripping are effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of surface coating, in particular to a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating and a preparation method thereof. BACKGROUND

[0002] Nickel-cobalt alloy coating is widely used in extreme environments such as aircraft engine blades, oil drilling tools, and key components of offshore platforms due to its excellent wear resistance and corrosion resistance. Traditional preparation methods such as plasma spraying and high-speed oxygen fuel spraying have defects such as high porosity, weak interlayer bonding force, and large residual stress. These defects become channels for corrosion medium penetration, leading to premature failure of the coating.

[0003] To solve the above problems, the prior art often adds rare earth elements or ultra-fine ceramic particles (such as WC and Cr3C2) for modification, or performs laser remelting post-processing to reduce porosity. However, these techniques do not focus on the surface physical and chemical state of the coating itself, and cannot endow it with hydrophobic properties. Hydrophobic properties can effectively repel corrosion droplets, which is an important way to improve corrosion resistance. Currently, methods for imparting hydrophobicity to materials mainly involve adding low-surface-energy substances (such as fluorinated polymers) or constructing micro-nano structures, but these external substances usually have poor wear resistance and will quickly fail under frictional conditions.

[0004] Therefore, it is of great industrial application value to develop a method for preparing a nickel-cobalt-based coating with high strength, high toughness, excellent corrosion resistance, and intrinsic hydrophobicity without the need for adding hydrophobic materials, by only innovating the preparation process. SUMMARY

[0005] The present application aims to overcome the shortcomings of the prior art and provide a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating and a preparation method thereof. This method innovatively combines substrate pretreatment, multi-layer gradient spraying, and key interlayer laser micro-texturing treatment, and simultaneously achieves significant improvements in wear resistance, corrosion resistance, and hydrophobicity of the coating without the need for any external hydrophobic additives.

[0006] To achieve the above-mentioned purpose, the present application provides the following technical solution: a preparation method of a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating, comprising the following steps: S1. The surface of the metal substrate is subjected to oil removal, sandblasting roughening treatment, then washed with anhydrous ethanol and dried; S2. Prepare a nickel-cobalt metal-based alloy powder composed of the following components by weight: nickel 55-65 parts, cobalt 20-30 parts, chromium 15-18 parts, molybdenum 4-6 parts, tungsten 3-5 parts, iron 1-3 parts, silicon 0.8-1.5 parts, carbon 0.5-1.2 parts, and boron 0.5-1.0 parts; S3. A layer of the alloy powder having a thickness of 50-100 μm was sprayed on the surface of the pretreated substrate using a supersonic flame spraying device as a base layer. The spraying parameters were: kerosene flow rate 22-26 L / h, oxygen flow rate 850-950 Nm³ / h, spraying distance 300-350 mm, and powder feed rate 35-45 g / min. S4. The surface of the bottom coating obtained in step S3 is scanned using a pulsed fiber laser with a laser power of 200-400 W, a scanning speed of 500-1500 mm / s, a pulse frequency of 20-50 kHz, and a spot overlap of 50%-70%. A regular micro-pit array with a diameter of 50-100 μm, a depth of 20-50 μm, and a spacing of 100-200 μm is formed on the coating surface. S5. After the bottom surface of S4 is treated, the alloy powder is sprayed using a supersonic flame spraying device to form an intermediate layer having a thickness of 100-200μm. The spraying parameters are the same or similar to those of S3. S6. Repeat steps S4 and S5: repeat n-1 times according to the total coating thickness, where n is the total number of layers, n ≥ 3; S7. After all cycles are completed, the final surface layer is sprayed, and then the outermost surface is quickly scanned using the pulsed fiber laser in low-power mode with a laser power of 100-200W and a scanning speed of 2000-3000mm / s to complete the preparation of the surface coating of the metal substrate.

[0007] Preferably, the nickel-cobalt metal-based alloy powder in step S2 has a particle size distribution of 15-53 μm and a sphericity greater than 90%.

[0008] Preferably, the laser microtexturing treatment in step S4 is performed under an inert gas protective atmosphere, wherein the inert gas is argon or nitrogen with a purity of 99.99% or more, and the gas flow rate is 15-25 L / min.

[0009] Preferably, the laser scanning path in step S4 is a cross scanning with an angle of 60° to each other, so that the formed micro-pit array is an equilateral triangle.

[0010] Preferably, the longitudinal section of the micro-pit in step S4 is U-shaped, and the angle between the side wall and the normal line of the coating surface is 10°-30°.

[0011] Preferably, the total number of layers n in step S6 is 3-5 layers, and the total coating thickness is controlled to be 300-600 μm.

[0012] Preferably, after the laser scanning in step S7, the coating is subjected to stress relief annealing treatment under argon protection at an annealing temperature of 550-650° C. for 1-2 hours, and then cooled to below 150° C. before being taken out of the furnace.

[0013] Preferably, in steps S3 and S5, the powder feeding gas of the supersonic flame spraying equipment is nitrogen, and the pressure is 0.7-0.9 MPa.

[0014] Preferably, in step S4, the wavelength of the pulsed fiber laser is 1064 nm.

[0015] Compared to existing technologies, the present invention provides a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating and its preparation method, which offers the following advantages: Through interlayer laser micro-texturing, a regular array of non-smooth micro-pits is created on the surface of the sprayed coating. Molten particles of the next sprayed layer embed into these micro-pits, creating a strong "mechanical interlocking" effect, significantly improving interlayer bond strength and shear resistance, effectively preventing interlayer misalignment and spalling.

[0016] The micro-pit structure forms a tortuous longitudinal expansion path within the coating, greatly extending the path for the corrosive medium to penetrate from the surface to the substrate, thereby significantly slowing the corrosion process. At the same time, the remelted dense layer formed by the rapid laser scanning at the bottom of the micro-pit closes the original pores and blocks the lateral corrosion channel.

[0017] The micron-scale protrusions created by laser microtexturing, combined with the naturally formed nanoscale roughness from subsequent sprayed particle deposition, form a stable micro-nano composite structure. This structure effectively traps air, forming an air film, resulting in super-hydrophobic properties exceeding 150°. This hydrophobicity stems entirely from the physical structure, rather than chemical modification, resulting in extremely high mechanical stability and durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a scanning electron microscope (SEM) image of a surface micropit array formed after interlayer laser microtexturing treatment in Example 1 of the present invention; Figure 2 This is a test diagram of the static water contact angle of the coating surface in Example 1 of the present invention; Figure 3 The figure is a bar graph showing the bonding strength test of the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0020] Figure 1Observe by SEM at an accelerating voltage of 15 kV, in secondary electron imaging mode, and the scale bar in the figure is 50 μm.

[0021] Figure 2 Use a contact angle measuring instrument (optical imaging method) to slowly drop deionized water as the test liquid at a volume of 2 μL onto the surface of the coating under the condition of room temperature (25 ± 2 °C) and a relative humidity of 50% to 60%, capture the water droplet profile by a high-definition CCD camera, and calculate the contact angle value by fitting with the matching software.

[0022] The coating bond strength test refers to the national standard GB / T 8642-2002 “Determination of Bond Strength of Thermal Sprayed Coating”; The test procedure is as follows: Sample preparation: process the coated sample into a standard tensile sample (a round bar with a diameter of 10 mm or a rectangular test block with a size of 50 mm x 25 mm), and keep the coating thickness in the original state (300-600 μm). Use a high-strength structural adhesive (such as epoxy resin adhesive) to bond the coating surface of the sample to a steel butt block of the same size, ensuring that the bonding surface completely covers the coating and is free of air bubbles. After curing at room temperature (25 ± 5 °C) for 24 h, polish the ends of the bonded sample with a grinding wheel to ensure uniform stress during tensile testing.

[0023] Equipment parameters: use a universal material testing machine (such as WE-30 type), with a range of 0-100 kN, and control the tensile rate at 1 mm / min.

[0024] Test process: clamp the sample in the upper and lower clamps of the testing machine, ensuring that the sample axis is consistent with the direction of the tensile force and avoiding additional bending moments. Start the testing machine and load uniformly until the coating separates from the substrate or the coating breaks, and record the maximum breaking load (F). Repeat at least 5 parallel samples for each test, and exclude abnormal values (data with a deviation of more than 15% from the average value).

[0025] Result calculation: bond strength (σ) = maximum breaking load (F) / bonding area of the coating and the butt block, unit: MPa.

[0026] The coating porosity test refers to the national standard GB / T 17407-2010 “Thermal Sprayed Coating Porosity Test Method”; Test procedure: Sample preparation: cut the sample perpendicular to the coating surface, polish the cross section with 400#, 800#, 1200#, and 2000# sandpaper in sequence, and then polish to a mirror surface with diamond polishing paste (particle size 1-2 μm). Corrode the cross section with a 4% volume fraction of nitric acid alcohol solution for 5-10 s to clearly show the coating structure.

[0027] Equipment parameters: optical microscope (such as BX53M type) with magnification of 500 times, equipped with image acquisition system and analysis software (such as Image-ProPlus).

[0028] Test process: images are collected in different areas (at least 5 non-overlapping fields of view) of the coating cross-section, and the area of each field of view is not less than 0.01 mm². The image is converted to a black and white binary image (pores are black and coating is white) by the analysis software, and the total area of the pores in each field of view is automatically counted.

[0029] Result calculation: porosity (P) = (total area of pores in all fields of view / total area of all fields of view) x 100%, and the average value is taken as the final result.

[0030] Coating microhardness test refers to national standard GB / T4340.1-2009 "Metallic Materials Vickers Hardness Test Part 1: Test Method"; Test steps: Sample preparation: the same as the sample preparation method of porosity test, polish the coating cross-section to a mirror surface (no scratches, no deformation).

[0031] Equipment parameters: microhardness tester (such as HV-1000 type), test force 200g (1.961N), holding time 15s, diamond indenter is a regular quadrangular pyramid (apex angle 136°).

[0032] Test process: 5 test points are uniformly selected in the thickness direction of the coating (avoiding the interface between the coating and the substrate by more than 10μm), and the distance between each point is not less than 3 times the length of the diagonal line of the indentation. Load to the set force value and keep for 15s, measure the length of the two diagonal lines (d1, d2) of the indentation after unloading, accurate to 0.1μm.

[0033] Result calculation: microhardness (HV) = 0.1891xF / (d1xd2), where F is the test force (N), d1 and d2 are the diagonal line lengths (mm), and the average value of the 5 points is taken as the result.

[0034] Self-corrosion potential test refers to national standard GB / T10123-2021 "Metallic and Alloy Corrosion Electrochemical Test Method"; Test steps: Sample preparation: cut the coating sample into a 10mm x 10mm square, seal the non-test surface with epoxy resin, and expose only a 1cm² coating surface as the working electrode. Clean the exposed surface with anhydrous ethanol before testing to remove oil stains, and dry naturally.

[0035] Apparatus and solution: Electrochemical workstation (e.g. CHI660E) was used, three-electrode system: working electrode was the coating sample, reference electrode was saturated calomel electrode (SCE), auxiliary electrode was platinum plate (1 cm x 1 cm). The corrosion medium was 3.5wt% NaCl solution (analytically pure NaCl + deionized water), and the solution temperature was controlled at 25 ± 1℃.

[0036] Test process: immerse the three electrodes in the NaCl solution, stand for 30 min, and wait for the electrode potential to be stable (potential change ≤1 mV / min). Open circuit potential test mode was used, and the potential value after stabilization was recorded, which was the self-corrosion potential (Ecorr), unit: V (vs. SCE).

[0037] Each group of tests was repeated at least 3 times, and the average value was taken.

[0038] Static water contact angle and rolling angle test refers to the national standard GB / T30693-2014 "Determination of contact angle of plastic film and sheet"; Test steps: Sample preparation: ensure that the coating surface is flat, free of oil stains and dust, and the surface is blown with compressed air before testing.

[0039] Apparatus parameters: contact angle measuring instrument (e.g. OCA20), microsyringe (5 μL), lens magnification 20 times.

[0040] Static water contact angle test: 5 μL of deionized water was added to the coating surface with a syringe, and the droplet was left to stand for 10 s after forming. The droplet profile was captured by the instrument lens, and the contact angle (the angle between the droplet and the coating surface) was calculated by elliptical fitting algorithm. Test at different areas (at least 5 points) of the sample, and take the average value as the result.

[0041] Rolling angle test: fix the sample on an inclinable platform, add 10 μL of deionized water, and slowly incline the platform (inclination rate 1° / s). Record the inclination angle of the platform when the droplet starts to roll, which is the rolling angle. Repeat the test 5 times, and take the average value as the result.

[0042] Example 1: a preparation method of a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating, specifically comprising the following steps: S1. Select 45# steel as the substrate, first use alkaline degreaser to ultrasonic degrease at 60℃ for 30 minutes, then use 80 mesh white corundum sand for sand blasting treatment, sand blasting pressure is 0.6 MPa, distance is 150 mm, then use anhydrous ethanol for ultrasonic cleaning for 10 minutes, dry in 80℃ oven for 2 hours; S2. Prepare a nickel-cobalt metal-based alloy powder consisting of the following components by weight: nickel 55 parts, cobalt 20 parts, chromium 15 parts, molybdenum 4 parts, tungsten 3 parts, iron 1 part, silicon 0.8 parts, carbon 0.5 parts, and boron 0.5 parts; the powder particle size distribution is 15-30 μm, and the sphericity is 92%; S3. Use a high-velocity oxygen fuel spraying device to spray a bottom layer on the surface of the pretreated substrate, with a thickness controlled at 50 μm; the spraying parameters are: kerosene flow rate 22 L / h, oxygen flow rate 850 Nm³ / h, spraying distance 300 mm, powder feeding rate 35 g / min, powder feeding gas nitrogen, and pressure 0.7 MPa; S4. Use a pulsed fiber laser with a wavelength of 1064 nm to scan the surface of the bottom layer, under the protection of argon gas with a purity of 99.99% and a gas flow rate of 15 L / min; the laser parameters are: power 200 W, scanning speed 500 mm / s, pulse frequency 20 kHz, and light spot overlap rate 50%; the scanning path is a cross-scan with an included angle of 60°, forming an equilateral triangle micro-pit array with a diameter of 50 μm, a depth of 20 μm, and a pitch of 100 μm; the longitudinal section of the micro-pit is U-shaped, and the included angle between the side wall and the normal line of the coating surface is 10°; S5. Continue to spray the alloy powder on the surface of the bottom layer treated in S4 to form an intermediate layer with a thickness of 100 μm, and the spraying parameters are the same as those in S3; S6. Repeat steps S4 and S5 each once, with a total number of layers n = 3, and a total coating thickness of about 350 μm; S7. Spray the last surface layer, and then use a pulsed fiber laser to quickly and lightly scan the outermost surface in a low-power mode, with a laser power of 100 W and a scanning speed of 2000 mm / s; then perform a stress relief annealing treatment under the protection of argon gas, with an annealing temperature of 550°C, a holding time of 1 hour, and a furnace cooling to below 150°C before discharging.

[0043] Example 2, S1. Select 45# steel as the substrate, first use an alkaline degreaser to ultrasonically remove oil at 60°C for 30 minutes, then use 80 mesh white corundum sand for sandblasting treatment, with a sandblasting pressure of 0.6 MPa and a distance of 150 mm, and then use anhydrous ethanol for ultrasonic cleaning for 10 minutes and drying in an 80°C oven for 2 hours; S2. Prepare a nickel-cobalt metal-based alloy powder consisting of the following components by weight: nickel 55 parts, cobalt 20 parts, chromium 15 parts, molybdenum 4 parts, tungsten 3 parts, iron 1 part, silicon 0.8 parts, carbon 0.5 parts, and boron 0.5 parts; the powder particle size distribution is 15-30 μm, and the sphericity is 92%; S3. Use a high-velocity oxygen fuel spraying device to spray a bottom layer, with a thickness controlled at 75 μm; the spraying parameters are: kerosene flow rate 24 L / h, oxygen flow rate 900 Nm³ / h, spraying distance 325 mm, powder feeding rate 40 g / min, powder feeding gas nitrogen, and pressure 0.8 MPa. S4. Laser processing parameters: power 300 W, scanning speed 1000 mm / s, pulse frequency 35 kHz, spot overlap rate 60%; argon flow rate 20 L / min; forming equilateral triangle micro-pit array with diameter 75 μm, depth 35 μm, and pitch 150 μm, micro-pit longitudinal section is U-shaped, and the included angle between the side wall and the normal of the coating surface is 20°; S5. Spraying intermediate layer, thickness 150 μm, spraying parameters are the same as S3; S6. Repeating steps S4 and S5 for 2 times, total layer number n = 4, and total coating thickness is about 500 μm; S7. Surface layer laser light scanning parameters: power 150 W, scanning speed 2500 mm / s; stress relief annealing temperature 600 ℃, holding time 1.5 hours; other conditions are the same as example 1.

[0044] Example 3, S1. Selecting 45# steel as the base material, first using alkaline degreaser to ultrasonic degrease at 60 ℃ for 30 minutes, then using 80 mesh white corundum sand for sand blasting treatment, sand blasting pressure is 0.6 MPa, distance is 150 mm, then using anhydrous ethanol for ultrasonic cleaning for 10 minutes, and drying in 80 ℃ oven for 2 hours; S2. Preparing nickel-cobalt metal-based alloy powder, which is composed of the following components by weight: nickel 65 parts, cobalt 30 parts, chromium 18 parts, molybdenum 6 parts, tungsten 5 parts, iron 3 parts, silicon 1.5 parts, carbon 1.2 parts, and boron 1.0 part; powder particle size distribution is 40-53 μm, and sphericity is 93%; S3. Using supersonic flame spraying equipment to spray the bottom layer, thickness is controlled to be 100 μm; spraying parameters are as follows: kerosene flow rate 26 L / h, oxygen flow rate 950 Nm³ / h, spraying distance 350 mm, powder feeding rate 45 g / min, powder feeding gas is nitrogen, and pressure 0.9 MPa; S4. Laser processing parameters: power 400 W, scanning speed 1500 mm / s, pulse frequency 50 kHz, spot overlap rate 70%; nitrogen flow rate 25 L / min; forming equilateral triangle micro-pit array with diameter 100 μm, depth 50 μm, and pitch 200 μm, micro-pit longitudinal section is U-shaped, and the included angle between the side wall and the normal of the coating surface is 30°; S5. Spraying intermediate layer, thickness 200 μm, spraying parameters are the same as S3; S6. Repeating steps S4 and S5 for 3 times, total layer number n = 5, and total coating thickness is about 600 μm; S7. Surface layer laser light scanning parameters: power 200 W, scanning speed 3000 mm / s; stress relief annealing temperature 650 ℃, holding time 2 hours; other conditions are the same as example 1.

[0045] Example 4, S1. 45# steel was selected as the substrate. First, an alkaline degreasing agent was used for ultrasonic degreasing at 60°C for 30 minutes, then sand blasting was performed using 80 mesh white corundum sand at a blasting pressure of 0.6 MPa and a distance of 150 mm, and then the sample was ultrasonically cleaned with anhydrous ethanol for 10 minutes and dried in an 80°C oven for 2 hours; S2. A nickel-cobalt metal-based alloy powder was prepared, with a chemical composition by weight parts as follows: nickel 62 parts, cobalt 28 parts, chromium 17 parts, molybdenum 5.5 parts, tungsten 4.5 parts, iron 2.5 parts, silicon 1.3 parts, carbon 1.0 parts, and boron 0.8 parts; the powder particle size distribution was 25-45 μm, and the sphericity was 96%; S3. An ultrasonic flame spraying device was used to spray the bottom layer, with a thickness controlled at 80 μm; the spraying parameters were as follows: kerosene flow rate 25 L / h, oxygen flow rate 920 Nm³ / h, spraying distance 330 mm, powder feeding rate 42 g / min, powder feeding gas nitrogen, and pressure 0.85 MPa; S4. Laser treatment parameters: power 350 W, scanning speed 1200 mm / s, pulse frequency 40 kHz, and light spot overlap rate 65%; argon flow rate 22 L / min; an equilateral triangle micro-pit array with a diameter of 80 μm, a depth of 40 μm, and a pitch of 160 μm was formed, the micro-pit longitudinal section was U-shaped, and the included angle between the side wall and the normal to the coating surface was 25°; S5. The middle layer was sprayed, with a thickness of 180 μm and the same spraying parameters as S3; S6. Steps S4 and S5 were repeated twice, for a total of n=4 layers, and the total coating thickness was about 550 μm; S7. Top layer laser light scanning parameters: power 180 W, scanning speed 2800 mm / s; stress relief annealing temperature 620°C, holding time 1.8 hours; other conditions were the same as in Example 1.

[0046] Comparative Example 1. Compared with Example 2, all the laser micro-texturing treatments of step S4 were omitted, and the remaining steps and parameters were the same.

[0047] Comparative Example 2. Compared with Example 2, only the laser treatment was performed after the last layer was sprayed, and the middle layer was not subjected to laser micro-texturing treatment, and the remaining steps and parameters were the same.

[0048] Comparative Example 3. Compared with Example 2, the laser power of step S4 was changed to 500 W, and the remaining steps and parameters were the same.

[0049] Comparative Example 4. Compared with Example 2, the alloy powder in step S2 did not contain tungsten, and the nickel content was increased to 64 parts, and the remaining steps and parameters were the same.

[0050] Comparative Example 5, compared with Example 2, only single layer spraying was performed, with a thickness of about 500 μm, without multi-layer spraying and laser treatment cycles, and the remaining steps and parameters were the same.

[0051] Comparative Example 6, compared with Example 2, the spraying distance of steps S3 and S5 was changed to 250 mm, and the remaining steps and parameters were the same.

[0052] The coatings obtained in Examples 1 to 4 and Comparative Examples 1 to 6 were grouped in turn as JSJ-TC-01, JSJ-TC-02, JSJ-TC-03, JSJ-TC-04, JSJ-TC-05, JSJ-TC-06, JSJ-TC-07, JSJ-TC-08, JSJ-TC-09, JSJ-TC-010, and performance tests were performed on the products of the examples and comparative examples, including bonding strength (MPa), porosity (%), microhardness (HV), self-corrosion potential (V vs. SCE), static water contact angle (°), and rolling angle (°), and the specific test results are shown in Tables 1 and 2.

[0053] Table 1

[0054] Table 2

[0055] The laser manufactured a regular array of micro-pits on the surface of the sprayed layer, and the next layer of molten particles embedded in the micro-pits to form a "mechanical interlocking" effect. The bonding strength of Example 2 reached 78 MPa, which was 50% higher than that of Comparative Example 2 with only the last layer treated by laser, and 73% higher than that of Comparative Example 1 without laser treatment, indicating that the interlayer micro-texture is the key to enhancing the bonding; the tortuous channels formed by the micro-pits lengthened the penetration path of the corrosion medium, and the laser remelting layer closed the horizontal pores, so that the self-corrosion potential of Example 2 was significantly positively shifted compared with Comparative Example 1, and the corrosion resistance was significantly improved, solving the problems of fast vertical penetration and easy horizontal corrosion diffusion of traditional coatings.

[0056] The micron protrusions of the laser micro-texture combined with the natural nanometer roughness of the sprayed particles to form a stable micro-nano composite structure. This structure can effectively capture air to form an air film. The static water contact angle of Example 2 was 156°, and the rolling angle was 4.2°, while the contact angle of Comparative Example 1 without laser treatment was only 105°, indicating that this structure can achieve super-hydrophobicity without chemical modification, and the wear resistance is much higher than that of the chemical modification layer.

[0057] In step 4 of the present invention, a laser power of 200-400W was used. However, in Comparative Example 3, excessive melting resulted in increased coating brittleness and a decrease in bonding strength to 60MPa. This indicates that the present invention achieves better bonding strength when the laser power is controlled within 200-400W. The spraying distance of the embodiment is 300-350mm, while in Comparative Example 6 (distance 250mm), the porosity increased to 2.1% due to overheating and oxidation of the particles, indicating that the porosity of the present invention is lower. The present invention utilizes a multi-layer structure; Comparative Example 5, a single-layer spraying method, resulted in a bonding strength of only 38MPa due to stress concentration. This indicates that a range of 3-5 layers yields higher bonding strength.

[0058] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent substitutions, or modifications based on the present invention to solve substantially the same technical problems and achieve substantially the same technical effects are all included in the scope of protection of the present invention.

Claims

1. A method for preparing a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating, characterized in that: The following steps are involved: S1. Degrease and sandblast the metal substrate surface, then clean it with anhydrous ethanol and dry it; S2. Preparation of nickel-cobalt metal-based alloy powder, consisting of the following components in parts by weight: 55-65 parts nickel, 20-30 parts cobalt, 15-18 parts chromium, 4-6 parts molybdenum, 3-5 parts tungsten, 1-3 parts iron, 0.8-1.5 parts silicon, 0.5-1.2 parts carbon, 0.5-1.0 parts boron; S3. A layer of the alloy powder having a thickness of 50-100 μm was sprayed on the surface of the pretreated substrate using a supersonic flame spraying device as a base layer. The spraying parameters were: kerosene flow rate 22-26 L / h, oxygen flow rate 850-950 Nm³ / h, spraying distance 300-350 mm, and powder feed rate 35-45 g / min. S4. The surface of the bottom coating obtained in step S3 is scanned using a pulsed fiber laser with a laser power of 200-400 W, a scanning speed of 500-1500 mm / s, a pulse frequency of 20-50 kHz, and a spot overlap of 50%-70%. A regular micro-pit array with a diameter of 50-100 μm, a depth of 20-50 μm, and a spacing of 100-200 μm is formed on the coating surface. S5. After the bottom surface of S4 is treated, the alloy powder is sprayed using a supersonic flame spraying device to form an intermediate layer having a thickness of 100-200μm. The spraying parameters are the same or similar to those of S3. S6. Repeat steps S4 and S5: repeat n-1 times according to the total coating thickness, where n is the total number of layers, n ≥ 3; S7. After all cycles are completed, the final surface layer is sprayed, and then the outermost surface is quickly scanned using the pulsed fiber laser in low-power mode with a laser power of 100-200W and a scanning speed of 2000-3000mm / s to complete the preparation of the surface coating of the metal substrate.

2. The method for preparing a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The particle size distribution of the nickel-cobalt metal-based alloy powder in step S2 is 15-53 μm, and the sphericity is greater than 90%.

3. The method for preparing a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The laser microtexturing treatment in step S4 is performed under an inert gas protective atmosphere, wherein the inert gas is argon or nitrogen with a purity of 99.99% or more, and the gas flow rate is 15-25 L / min.

4. The method for preparing a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The laser scanning path in step S4 is a cross scanning with an angle of 60° between each other, so that the formed micro-pit array is an equilateral triangle.

5. The method for preparing a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The longitudinal section of the micro-pit in step S4 is U-shaped, and the angle between the side wall and the normal line of the coating surface is 10°-30°.

6. The method for preparing a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The total number of layers n in step S6 is 3-5 layers, and the total coating thickness is controlled to be 300-600 μm.

7. The method for preparing a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: After the laser light sweeping in step S7, the coating is subjected to stress relief annealing treatment under argon protection at an annealing temperature of 550-650° C. for 1-2 hours, and then cooled to below 150° C. before being taken out of the furnace.

8. The method for preparing a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: In steps S3 and S5, the powder feeding gas of the supersonic flame spraying equipment is nitrogen, and the pressure is 0.7-0.9 MPa.

9. The method for preparing a nickel-cobalt metal-based wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: In step S4, the wavelength of the pulsed fiber laser is 1064 nm.

10. A nickel-cobalt metal-based wear-resistant and corrosion-resistant coating prepared by the method according to any one of claims 1 to 9, characterized in that: The bonding strength between the coating and the substrate is ≥70 MPa, the porosity is <1%, the microhardness is ≥HV650, the self-corrosion potential in 3.5wt% NaCl solution is ≥-0.25V, the static water contact angle is ≥150°, and the rolling angle is ≤5°.

Citation Information

Patent Citations

  • Preparation method for inconel alloy based self-lubricating corrosion and wear resistant coating

    CN102424943A

  • Friction structure, friction part and compressor

    CN110374881A

  • Preparation method of sinusoid gradient micro-texture plasma coating

    CN113463007A

  • Preparation method of nickel-cobalt-based low-temperature supersonic spraying-laser accompanying strengthening coating and coating

    CN115896674A

  • Method of coating of a substrate with a thermal spray coating material and coated substrate formed thereby

    US20130209745A1

Cited By

  • Centrifugal casting method of bearing and bearing

    CN121272406A